Educational chatting system - Ng, Eng Chui (2010)
Chatting system is a program developed for students in delivering their message to another student by using the chatting system program. It also provides offline messages to be delivered once the user online or sign in to the chatting system. It Is useful when students use this chatting system to discuss their assignments or projects without going out for an outdoor meeting. The chatting system is based on peer to peer concept where student need to initialize server in order to sign in to the chatting system. Without the present of Internet, student or user will still available to connect to the chatting system and deliver the messages. This means that the chatting system working in local area network environment. Username and password are required as authentication to get sign in to the chatting system. Besides, the chatting system must fulfill the function of delivering message in a local area network. As a result, the chatting system can help students in delivering the message to recipient successfully. Lastly, students can benefit from the chatting system in discussing on assignments and projects by sending messages to each other.